Politická kultura v narativech: kulturní repertoáry vztahování se k současné politice - Miroslav Grznár; Petra Beránková; Lucie Černá; Tomáš Samec (AntropoWebzin)
Political culture as a concept is an interdisciplinaryissue balancing between culturalanthropology, political science and sociology.This article presents conclusions of qualitativeresearch of contemporary czech political culture.Our research is based on 35 narrative interviewsconducted by students with their parents. We caninfer from quantitative studies that the level oftrust in the political system, institutions and actorshas hit the bottom. These studies are not ableto describe all aspects of political culture. Fromour position of interpretative paradigm we aimto analyse cultural repertoires through which isthe political situation narratively reconstructed.We perceive narrative as a performative genre ofrefering to social reality. We have identified thefollowing repertoires: 1. interested, 2. objective,3. evasive and 4. alienated. We have found fourtypes of layman’s theories, which were used bynarrators to explain the drop of trust in politics: 1.communist past 2. the nature of the Czech nation3. fatalistic theories of power 4. theories of “thesedays”.